2022
DOI: 10.1038/s41598-022-09331-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel renal perivascular mesenchymal cell subset gives rise to fibroblasts distinct from classic myofibroblasts

Abstract: Perivascular mesenchymal cells (PMCs), which include pericytes, give rise to myofibroblasts that contribute to chronic kidney disease progression. Several PMC markers have been identified; however, PMC heterogeneity and functions are not fully understood. Here, we describe a novel subset of renal PMCs that express Meflin, a glycosylphosphatidylinositol-anchored protein that was recently identified as a marker of fibroblasts essential for cardiac tissue repair. Tracing the lineage of Meflin+ PMCs, which are fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…However, an important caveat is that in the present study pancreatic tissues 12 days post-PDL were assessed to avoid systemic toxicity of DTx administration in Meflin-ZDC mice, leaving the question open as to whether PSCs are primarily involved in regenerative and reparative or persistent fibrotic response after pancreatic injury. Interestingly, we and others previously found that Meflin is also expressed by fibroblasts in the heart, lung, kidney, and intestine, wherein it plays roles by providing protection against fibrosis and promoting tissue repair after tissue injuries [23,33,52,53]. Taken together with the present study, these studies will contribute to the understanding of the beneficial roles of fibroblasts in physiology and pathology.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…However, an important caveat is that in the present study pancreatic tissues 12 days post-PDL were assessed to avoid systemic toxicity of DTx administration in Meflin-ZDC mice, leaving the question open as to whether PSCs are primarily involved in regenerative and reparative or persistent fibrotic response after pancreatic injury. Interestingly, we and others previously found that Meflin is also expressed by fibroblasts in the heart, lung, kidney, and intestine, wherein it plays roles by providing protection against fibrosis and promoting tissue repair after tissue injuries [23,33,52,53]. Taken together with the present study, these studies will contribute to the understanding of the beneficial roles of fibroblasts in physiology and pathology.…”
Section: Discussionsupporting
confidence: 76%
“…It is noted that ZsGreen expression from the ZDC allele was so low in the pancreas that it did not affect the observation of mGFP fluorescence. Furthermore, we subjected the pancreata of Meflin-ZDC; LSL-mTmG mice to in vivo vascular staining by intravenous injection of an anti-CD31 antibody and isolectin B4, which binds to the endothelial cell surface [32,33], followed by tissue clearing [34] and three-dimensional (3D) observation by confocal microscopy (supplementary material, Figure S6B-D, Movies S1 and S2). The data showed that most Meflin + PSCs extend their long and thin cytoplasmic protrusions on the abluminal surface of the capillary lumen.…”
Section: Meflin Is a Psc Marker 65mentioning
confidence: 99%
“…The roles of rCAFs in rare types of cancer remain elusive [ 67 , 68 ]. Interestingly, Meflin + fibroblasts have been found in the stroma of non-tumor fibrotic diseases, such as cardiac fibrosis, idiopathic pulmonary fibrosis, and kidney fibrosis, where they seem to be essential for tissue repair, but also play a role in suppressing fibrosis, unlike α-SMA + myofibroblasts, which promote tissue fibrosis and stiffening [ 40 , 69 , 70 ]. These findings suggest common mechanisms and etiologies of cancer and fibrotic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, no approved therapies for CKD are currently available. The final common pathway of CKD is fibrosis caused by the activation of interstitial fibroblasts to myofibroblasts, increased secretion and accumulation of the extracellular matrix, and loss or perturbation of tissue-specific epithelial cells and other cell lineages 3 5 .…”
Section: Introductionmentioning
confidence: 99%